Kadar Fosfat, Nitrat dan Silikat di Teluk Jakarta - Marojahan Simanjuntak (Universitas Gadjah Mada, 2007)
The aim of this study was to find out the distribution pattern of phosphate, nitrate and silicate in the Jakarta Bay. The research were carried out in May and October 2004. Water samples were collected from 30 stations at surface and buttom layers using Nansen Bottle Sampler. Samples were analyzed using spectofotometer for phosphate, nitrate and silicate concentrations. The results showed that in May 2004, concentration of phosphate (0.03-0.05 ppm) and nitrate 90.05-0.29 ppm) were the highest in the western area, while in the central part, phosphate (0.002-0.07 ppm) and nitrate (0.05-0.29 ppm) were the lowest, respectively. In contrast to silicate, the highest was (0.61-2.93 ppm) found in the eastern part and the lowest (0.43-1.05 ppm) occurred in the western part. In October 2004, the highest concentration for phosphate (0.01-0.11 ppm) was found in eastern part, nintrate (0.03-0.19 ppm) and silicate (0.34-3.54 ppm) were found in central part, respectively. While the lowest for phosphate (0.007-0.06 ppm) occurred in central part, nitrate (0.015-0.15 ppm) in western part and silicate (0.31-1.77 ppm) in eastern part, respectively. It was suggested to manage water discharge into the Bay to reduce eutrophication.